2001
DOI: 10.1046/j.1365-294x.2001.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep molecular divergence in the absence of morphological and ecological change in the Californian coastal dune endemic trapdoor spiderAptostichus simus

Abstract: Aptostichus simus is a trapdoor spider endemic to the coastal dunes of central and southern California and, on morphological grounds, is recognized as a single species. Mitochondrial DNA 16S rRNA sequences demonstrate that most populations are fixed for the same haplotype and that the population haplotypes from San Diego County, Los Angeles County, Santa Rosa Island, and Monterey County are extremely divergent (6-12%), with estimated separation times ranging from 2 to 6 million years. A statistical cluster ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 50 publications
8
155
1
1
Order By: Relevance
“…Th eir results suggested that a morphological species concept could greatly underestimate true evolutionary diversity since spider genitalia may not evolve as rapidly and divergently as previously believed (Bond et al 2001;Hedin 1997). Morphospecies demonstrating high genetic divergence without comparable morphological divergence may therefore represent species complexes (Bond et al 2001). Pardosa groenlandica, one of the species that was widely sampled in this study, and with high intraspecifi c divergence value (max =3.87%), may also represent a species complex but may not be completely cryptic.…”
Section: Potential Causes Of Anomalous Values In Published Datamentioning
confidence: 69%
See 2 more Smart Citations
“…Th eir results suggested that a morphological species concept could greatly underestimate true evolutionary diversity since spider genitalia may not evolve as rapidly and divergently as previously believed (Bond et al 2001;Hedin 1997). Morphospecies demonstrating high genetic divergence without comparable morphological divergence may therefore represent species complexes (Bond et al 2001). Pardosa groenlandica, one of the species that was widely sampled in this study, and with high intraspecifi c divergence value (max =3.87%), may also represent a species complex but may not be completely cryptic.…”
Section: Potential Causes Of Anomalous Values In Published Datamentioning
confidence: 69%
“…Within single populations in California, Bond et al (2001) found haplotypes of the trapdoor spider Aptostichus simus with divergences ranging from 6-12%. Th eir results suggested that a morphological species concept could greatly underestimate true evolutionary diversity since spider genitalia may not evolve as rapidly and divergently as previously believed (Bond et al 2001;Hedin 1997). Morphospecies demonstrating high genetic divergence without comparable morphological divergence may therefore represent species complexes (Bond et al 2001).…”
Section: Potential Causes Of Anomalous Values In Published Datamentioning
confidence: 99%
See 1 more Smart Citation
“…1) suggest that speciation probably occurs initially by isolation of populations to small geographic areas, with ecological divergences developing later, if at all. This pattern is known in many low vagility, ecologically and morphologically conservative invertebrates (Bond et al 2001). However, the presence of recently evolved/ecologically and morphologically distinct populations with low sequence divergence ( fig.…”
Section: Species Delimitation In Xantusiamentioning
confidence: 84%
“…Yet, there are limited genetic data to substantiate this assumption. Several studies report genetic differentiation within and among populations of subsocial spiders, as a result of philopatry, restricted dispersal, or founder events (Johannesen et al 1998, Johannesen and Lubin 1999Bond et al 2001;Pedersen and Loeschcke 2001). In contrast, population genetic studies of solitary species document low genetic differentiation despite a bias towards investigations of species that are suspected to be restricted in either dispersal ability or habitat availability (Ramirez and Fandino 1996;Boulton et al 1998;Ramirez and Haakonsen 1999;Tso et al 2002;Bonte et al 2003).…”
mentioning
confidence: 99%